Does Psychoeducation Added to Oncology Rehabilitation Improve Physical Activity and Other Health Outcomes? A Systematic Review. Issue 2 (April 2017) - Dennett, Amy M.; Shields, Nora; Peiris, Casey L.; Reed, Melissa S.; O'Halloran, Paul D.; Taylor, Nicholas F.
Abstract : Background: Oncology rehabilitation programs improve a variety of health outcomes in cancer survivors. However, little is known about what components of rehabilitation are essential for improving outcomes. Objective: To evaluate the effectiveness of psychoeducational interventions added to exercise rehabilitation programs for cancer survivors. Methods: Electronic databases MEDLINE, EMBASE, PsycINFO, CINAHL, PubMed, and PEDro were systematically searched from the earliest available time to March 2016. Randomized controlled trials describing psychoeducational interventions added to exercise programs for cancer survivors were included for review. The primary outcome of interest was physical activity measured either subjectively or objectively. Meta-analyses using standardized mean differences were used to synthesize data. Risk of bias within trials was evaluated using the PEDro scale and between trials was assessed using the Grades of Research, Assessment, Development and Evaluation (GRADE) approach. Results: Six articles reporting outcomes from 2 trials were included for review. There was low- to high-quality evidence that there was no difference between exercise rehabilitation programs that included psychoeducation and exercise-only programs for improving physical activity levels, exercise capacity, general quality of life, and disease-specific quality of life. It is possible that exercise interventions alone include psychological elements that affect behavior change. Conclusion: There is insufficient evidence to support adding psychoeducational interventions to exercise-based oncology rehabilitation programs. More fully powered trials that directly compare different rehabilitation models are required to determine the most effective oncology rehabilitation model to improve health outcomes in cancer survivors.